Effects of elicitors in improving morphophysiological traits and biochemical activities in chilli (Capsicum annuum L.) in soilless culture - Awang, Noor Asma'a (2013)
Modern agriculture relies heavily on pesticides for the control of pests and diseases infestations in chilli plants. Without any effective control measures, plants disease could reduce chilli yields up to 95%. Concerning the negative impact of extensive pesticides used to human health and ecosystem, a number of recent researches are now focusing on alternative tools in an effort to reduce or eliminate yield losses and maintain high product quality. In the present study, attempts were made using natural plant elicitors like jasmonic acid (JA), salicylic acid (SA) and ethylene (ET) at different concentration (0.5, 1.0 and 1.5mM). These elicitors were applied as foliar sprays aiming to enhance plant health by induce resistance to reduce the risk of pest entry in chilli plant. Results show that different concentrations of elicitors significantly improved dry matter accumulation in the leaves, stems and roots, and resulting in increased chilli yield. Applications of 0.5mM jasmonic acid (JA) or 1.5mM salicylic acid (SA) gave the strongest positive effect compared to other treatment combinations. Therefore, further experiment was carried out to determine the effects of both selected elicitors on the growth and yield of chilli. The result showed that jasmonic acid treated plants significantly enhance plant health by improving plant growth and performance, stem and canopy diameter, photosynthesis rate and yield production compared to salicylic acid treated plants. Jasmonic acid was the best elicitor although there was a significant decrease in yield compared with pesticide treated plants. This negative effect on yield may have been due to under dosage of jasmonic acid application and heavy rainfall that occurred shortly after treatments. Another study was carried out to improve effectiveness of JA by increasing the frequency of application. The finding shows that jasmonic acid sprayed twice (JA2) had significantly in enhancing plant health by improved chilli plant growth and physiology in term of relative chlorophyll content, stomatal conductance, chlorophyll fluorescence and photosynthesis rate, thus enabling it to be more resistant to pests and diseases infestations which leads to improve chilli production. The mean values of peroxidase for inducible enzymes which have a role in plant resistance at vegetative stage were significantly higher in chilli plants treated with jasmonic acid. Enzymatic activity (Guaicol Peroxidase, Ascorbate Peroxidase and Catalase) was lowest in the untreated plants, which corresponded with the lower plant growth and physiological responses of unhealthy plant. Thus, it could be concluded that jasmonic acid are importance in enhancing plant health with induces resistance thus leading to better plant growth and improved chilli production which could be replace application of pesticide.